Multi-Resolution-Analysis-based Line-to-Ground Fault Detection in a VSC-Based HVDC System. Issue 4 (3rd July 2020) - Kar Ray, Debopoma; Chattopadhyay, Surajit; Sengupta, Samarjit
Abstract : This paper deals with the identification of single line-to-ground (LG) fault in a voltage source controller based high voltage direct current (HVDC) link, monitoring the multi-resolution-analysis (MRA)-based discrete wavelet transform (DWT) coefficients. A prototype model has been developed to assess the system at normal and at LG fault at the receiving end of the HVDC link, monitoring the AC sending end current in the system. This study also deals with the assessment of locations of LG faults in the HVDC link at different positions, from the sending end. Case studies have been carried out using field data and different DWT-based statistical parameters have been estimated and their variations due to fault have been observed. Then DWT-level-based optimization and parametric optimization have been done. An algorithm has been developed for fault assessment. Based on the specific outcome of the case studies, distance relaying scheme has been proposed, which has been validated with software simulation based on real field data.